Chronic obstructive pulmonary disease and functioning: implications for rehabilitation based on the ICF framework. (7th January 2013) - Jácome, Cristina; Marques, Alda; Gabriel, Raquel; Figueiredo, Daniela
Abstract: Purpose : This study aimed to describe the functioning of patients with Chronic Obstructive Pulmonary Disease (COPD) according to the International Classification of Functioning, Disability and Health (ICF) framework to inform future rehabilitation interventions. Method : A cross-sectional study with a convenience sample of outpatients with COPD was conducted. Data were collected using the Comprehensive ICF Core Set for Obstructive Pulmonary Diseases. Descriptive and inferential statistics were applied. Results : In total, 119 participants (71.43% male) with a mean age of 68.71 ± 11.61 years old were included. The frequency and extent of the majority of the impairments assessed were similar among participants at different COPD grades. The most relevant (frequency >70%) Body functions and structures impairments were related to exercise tolerance functions, sensations associated with cardiovascular and respiratory functions and respiratory system structure. Mobility and domestic life restrictions were the most frequently reported in the activities and participation component. Products for personal consumption, immediate family, health professionals and their attitudes were most frequently understood as facilitators whilst climate and air quality were perceived as barriers. Conclusions : Recommendations were drawn from this study in order to improve comprehensive rehabilitation interventions for patients with COPD based on ICF framework. Implications for Rehabilitation: Functioning of patients with Chronic Obstructive Pulmonary Disease can be comprehensively assessed in a worldwide common language – the International Classification of Functioning, Disability and Health. Rehabilitation interventions for patients with Chronic Obstructive Pulmonary Disease should be designed according to the International Classification of Functioning, Disability and Health framework, i.e. assessing and monitoring Body functions, Body structures, Activities and participation and Environmental factors.